Perspectives of paediatric and adult gastroenterologists on transfer and transition care of adolescents with inflammatory bowel disease. Issue 5 (May 2014) - Wright, E. K.; Williams, J.; Andrews, J. M.; Day, A. S.; Gearry, R. B.; Bampton, P.; Moore, D.; Lemberg, D.; Ravikumaran, R.; Wilson, J.; Lewindon, P.; Radford‐Smith, G.; et al.
Abstract Background Programmes specific to inflammatory bowel disease (IBD) that facilitate transition from paediatric to adult care are currently lacking. Aim We aimed to explore the perceived needs of adolescents with IBD among paediatric and adult gastroenterologists and to identify barriers to effective transition. Methods A web‐based survey of paediatric and adult gastroenterologists in Australia and New Zealand employed both ranked items (Likert scale; from 1 not important to 5 very important) and forced choice items regarding the importance of various factors in faciitating effective transition of adolescents from paediatric to adult care. Results Response rate among 178 clinicians was 41%. Only 23% of respondents felt that adolescents with IBD were adequately prepared for transition to adult care. Psychological maturity (Mean = 4.3, standard deviation (SD) = 0.70) and readiness as assessed by adult caregiver (Mean = 4, SD = 0.72) were prioritised as the most important factors in determining timing of transfer. Self‐efficacy and readiness as assessed by adult caregiver were considered the two most important factors to determine timing of transition by both groups of gastroenterologists. Poor medical and surgical handover (Mean = 4.10, SD = 0.8) and patients' lack of responsibility for their own care (Mean= 4.10, SD = 0.82) were perceived as major barriers to successful transition by both paediatric and adult gastroenterologists. Conclusions Deficiencies exist in current transition care of adolescents with IBD in Australia and New Zealand. Standardising transition care practices with strategies aimed at optimising communication, patient education, self‐efficacy and adherence may improve outcomes.